Sirtuin 2 (SIRT2): Confusing Roles in the Pathophysiology of Neurological Disorders - Chen, Xiuqi; Lu, Wenmei; Wu, Danhong (Frontiers in Neuroscience, 2021)
As a type of nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases, sirtuin 2 (SIRT2) is predominantly found in the cytoplasm of cells in the central nervous system (CNS), suggesting its potential role in neurological disorders. Though SIRT2 is generally acknowledged to accelerate the development of neurological pathologies, it protects the brain from deterioration in certain circumstances. This review summarized the complex roles SIRT2 plays in the pathophysiology of diverse neurological disorders, compared and analyzed the discrete roles of SIRT2 in different conditions, and provided possible explanations for its paradoxical functions. In the future, the rapid growth in SIRT2 research may clarify its impacts on neurological disorders and develop therapeutic strategies targeting this protein.